Genipin Induces Autophagy and Suppresses Cell Growth of Oral Squamous Cell Carcinoma via PI3K/AKT/MTOR Pathway - Wei M; Wu Y; Liu H; Xie C (Dove Medical Press, 2020)
MingBo Wei,1 YanLi Wu,2 Hui Liu,1 Chun Xie3 1Department of Stomatology, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People’s Republic of China; 2Department of Pharmacy, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People’s Republic of China; 3Stomatology Center, Affiliated Union Hospital of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 430022, People’s Republic of ChinaCorrespondence: Chun XieStomatology Center, Affiliated Union Hospital of Tongji Medical College, Huazhong University of Science and Technology, NO. 1277 Jiefang Avenue, Wuhan 430022, Hubei, People’s Republic of ChinaTel +8627-84309882Email a1aw9vf@sina.comBackground: Oral squamous cell carcinoma (OSCC) is a common malignant tumor of the head and neck, and it accounts for more than 90% of oral cancer. Due to high mortality, limitations of traditional treatment and many complications, new treatment methods are urgently needed. This study aimed to look into the effect of new potential anti-tumor drug, genipin, on OSCC treatment.Methods: In vitro, CCK-8, colony formation, and flow cytometry were used to detect the effect of genipin on SCC-9 and SCC-15 cell lines. Immunofluorescence, real-time PCR, and Western blotting were used to investigate its mechanism. Xenograft tumor model was used to explore the role of genipin in vivo.Results: We found that genipin suppressed cell growth and induced apoptosis in vitro. In addition, the expression of p62 was down-regulated while Beclin1 and LC3II were up-regulated in SCC-25 and SCC-9 cells. 3-methyladenine (3-MA) significantly decreased LC3 (LC3II)+ puncta, but genipin rescuect 3d this reduction. Furthermore, genipin also reduced the expression of p-PI3K, p-AKT, and p-mTOR. In vivo experiment showed that genipin significantly curbed the tumor size and weight. The positive expression of Ki67 protein and number of apoptotic cells were increased.Conclusion: Conclusively, this study implicated that genipin suppresses cell proliferation and stimulated apoptosis, and is the first exploration showing that genipin induces OSCC cell autophagy via PI3K/AKT/mTOR pathway inhibition.Keywords: genipin, oral squamous cell carcinoma, autophagy, PI3K/AKT/mTOR pathway